2010
DOI: 10.1109/tmc.2009.124
|View full text |Cite
|
Sign up to set email alerts
|

Superdiffusive Behavior of Mobile Nodes and Its Impact on Routing Protocol Performance

Abstract: Abstract-Mobility is the most important component in mobile ad-hoc networks (MANETs) and delay-tolerant networks (DTNs).In this paper, we first investigate numerous GPS mobility traces of human mobile nodes and observe super-diffusive behavior in all GPS traces, which is characterized by a 'faster-than-linear' growth rate of the mean square displacement (MSD) of a mobile node. We then investigate a large amount of access point (AP) based traces, and develop a theoretical framework built upon continuous time ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 51 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Within this paper, we will mainly focus on the analysis at the population level. Physicists have long been studying diffusion processes in different systems, and recently anomalous diffusive properties have been reported in many human activities, including human spatial movement [9][10][11] , and information foraging 12 . In a previous study of skin gambling 8 , we have shown that in a parimutuel betting game (where players gamble against each other), a gambler's net income displays a crossover from superdiffusion to normal diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Within this paper, we will mainly focus on the analysis at the population level. Physicists have long been studying diffusion processes in different systems, and recently anomalous diffusive properties have been reported in many human activities, including human spatial movement [9][10][11] , and information foraging 12 . In a previous study of skin gambling 8 , we have shown that in a parimutuel betting game (where players gamble against each other), a gambler's net income displays a crossover from superdiffusion to normal diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…These values of γ produce super-diffusion patterns and can be modeled using Lévy walk processes -step lengths have infinite variance. Kim et al, (144) analyze several human GPS mobility traces showing super-diffusive behavior and its impact on contact-based metrics.…”
Section: Introductionmentioning
confidence: 99%